MALIGNANT SACROCOCCYGEAL YOLK SAC (ENDODERMAL SINUS) TUMOR - Mufti, Tariq; Khan, M. Saeed; Dua, Muzher -U-; Waqar, Farah (Journal of Ayub Medical College Abbottabad, 2002)
We report a 2 ½ years old female child who presented with Malignant Sacrococcygeal Yolk sac (Endodermal Sinus) tumor as presacral mass with ulceration of overlying skin. Her ultrasonography (USG)abdomen revealed a huge presecral mass with irregular margins extending in to the pelvis, pushing the rectum antero-laterally. CT scanning of abdomen confirmed USG finding with out enlargement of retroperitoneal lymph nodes and no involvement of the liver. Serum AFP was abnormally elevated. The tumor was excised along with Coccyx in-toto through posterior approach dividing the sacrum and 3-Drugs (VAC) Chemotherapy started post-operatively i.e. 2-weeks after surgery. Here we discuss our experience with this extremely rare malignant extra-gonadal germ-cell tumor and review of literature. ’˜We can say with some assurance that although children may be victims of fate, they will not be the victims of our neglect (John F Kennedy)(1)’